Concentrations of interleukin 6 and tumour necrosis factor in serum and stools of children with Shigella dysenteriae 1 infection. Issue 2 (February 1993) - de Silva, D G; Mendis, L N; Sheron, N; Alexander, G J; Candy, D C; Chart, H; Rowe, B
Abstract : Serum interleukin 6 (IL-6) and tumour necrosis factor (TNF) were measured in children with dysentery during an epidemic caused by Shigella dysenteriae 1. IL-6 and TNF were also measured in fresh stool filtrates from children with acute gastroenteritis. The median serum IL-6 concentration was raised significantly in the children with complications (haemolytic uraemic syndrome, leukemoid reaction, thrombocytopenia, thrombocytosis, and severe colitis lasting more than one week) during the first week (n = 18, 9-7728 pg/ml; median 107) and in the second week (n = 13, 5-312 pg/ml; median 77), compared with convalescent sera (n = 10, < 3-85 pg/ml; median 39; p < 0.02 and < 0.05 respectively). The median IL-6 concentration during the first week was significantly higher in the group with complicated disease than in those with no complications (n = 8, < 3-37 pg/ml; median 5; p < 0.001). Although serum TNF concentrations were significantly raised in the complicated group during the first and second weeks of the illness and in the uncomplicated group compared with convalescence, there was no significant difference in the TNF concentrations between the complicated and uncomplicated groups. IL-6 was detectable in stool filtrates from eight of 13 children with S dysenteriae 1 infection and four of eight children with S flexneri infection. It was not detectable in Cryptosporidia, rotavirus, or adenovirus infections, those with pathogen-negative acute diarrhoea or controls. Seven of 13 children with S dysenteriae 1 and three of nine children with S flexneri infections had TNF detectable in stools. None of the children with Salmonella, Cryptosporidia, rotavirus of children with pathogen-negative diarrhoea and controls had detectable TNF in stool filtrates. It is postulated that the local and generalised vasculitis observed in shigellosis may be related to a direct effect of Shiga toxin on endothelial cells or caused by cytokine production stimulated by endotoxin, or both.